But seriously: what do algorithms want? Implying collective intentionalities in algorithmic relays. A distributed cognition approach - Toscano, Javier (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
Describing an algorithm can provide a formalization of a specific process. However, different ways of conceptualizing algorithms foreground certain issues while obscuring others. This article attempts to define an algorithm in a broad sense as a cultural activity of key importance to make sense of socio-cognitive structures. It also attempts to develop a sharper account on the interaction between humans and tools, symbols and technologies. Rather than human or machine-centered analyses, I draw upon sociological and anthropological theories that underline social practices to propose expanding our understanding of an algorithm through the notion of ‘collective intentionalities’. To make this term clear, a brief historical review is presented, followed by an argumentation on how to incorporate it in an integral perspective. The article responds to recent debates in critical algorithm studies about the significance of the term. It develops a discussion along the lines of cognitive anthropology and the cognitive sciences, therefore advancing a definition that is grounded in observed practices as well as in modeled descriptions. The benefit of this approach is that it encourages scholars to explore cognitive structures via archaeologies of technological assemblages, where intentionalities play a defining role in understanding socio-structured practices and cognitive ecologies.